Pathotypic characterization of Newcastle disease virus isolated from vaccinated chicken in West Java, Indonesia - Dwi Desmiyeni Putri; Ekowati Handharyani; Retno Damajanti Soejoedono; Agus Setiyono; Ni Luh Putu Ika Mayasari; Okti Nadia Poetri (Veterinary World, 2017)
ABSTRACT Aim: This research was conducted to differentiate and characterize eight Newcastle disease virus (NDV) isolates collected from vaccinated chicken at commercial flocks in West Java, Indonesia, in 2011, 2014 and 2015 by pathotype specific primers.